Penyelesaian Perselisihan Hasil Pemilihan Umum Serentak dalam Perspektif Keadilan - Sigit Nurhadi Nugraha (AL WASATH Jurnal Ilmu Hukum, 2023)
The Constitutional Court has the authority to resolve disputes over the results of general elections and local elections. Trial process of election and local election result disputes is based on formal aspects which aim to fulfill formal legal certainty, but sometimes formal legal certainty overrides aspects of justice, for example by not examining lawsuit if they do not meet the formal requirements (fail at the dismissal stage) so that attention is needed so that formal procedures are carried out in the Constitutional Court guarantees material / substantial justice. This paper uses a type of doctrinal normative research. The author concludes that justice can be achieved by fulfilling formal and material truths. So far, the Constitutional Court in resolving disputes over election results has prioritized formal truth by enforcing rules that are formal in nature, but formal truth does not necessarily reflect material truth. Even though the Constitutional Court upholds formal law, it is hoped that it will also uphold material law by not imposing a dismissal procedure , or even though there is, a dismissal procedure is applied after examining evidence.